To solve the equation \( 6(2x + 4) = 6x + 30 \), we will start by distributing the \( 6 \) on the left-hand side.
-
Distribute \( 6 \) to \( 2x \) and \( 4 \): \[ 6 \cdot 2x + 6 \cdot 4 = 12x + 24 \] So the equation becomes: \[ 12x + 24 = 6x + 30 \]
-
Next, subtract \( 6x \) from both sides to get all the \( x \) terms on one side: \[ 12x - 6x + 24 = 30 \] This simplifies to: \[ 6x + 24 = 30 \]
-
Now, subtract \( 24 \) from both sides: \[ 6x = 30 - 24 \] Simplifying the right side gives: \[ 6x = 6 \]
-
Divide both sides by \( 6 \): \[ x = 1 \]
Thus, the solution to the equation \( 6(2x + 4) = 6x + 30 \) is \[ \boxed{1} \]